2018
DOI: 10.1108/jima-11-2016-0082
|View full text |Cite
|
Sign up to set email alerts
|

Does gender differences play any role in intention to adopt Islamic mobile banking in Pakistan?

Abstract: Purpose Tremendous growth and worldwide expansion of Islamic banking industry has gained widespread attention of economist, bankers, investors and financial experts regardless of economic and political volatility in global banking industry. To compete with conventional banking, Islamic banks are setting up themselves with innovative technologies to gain competitive edge and market share. The establishment of mobile banking has been proven a technological wonder by eliminating time and space boundaries, and one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 61 publications
2
36
0
4
Order By: Relevance
“…Kaakeh et al (2018) showed that men have a greater tendency to use Islamic banks services. Haider et al (2018) stated that there are significant differences in intention to adopt Islamic mobile banking in Pakistan. Men are more likely to use Islamic mobile banking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaakeh et al (2018) showed that men have a greater tendency to use Islamic banks services. Haider et al (2018) stated that there are significant differences in intention to adopt Islamic mobile banking in Pakistan. Men are more likely to use Islamic mobile banking.…”
Section: Discussionmentioning
confidence: 99%
“…Kaakeh, Hassan, & van Hemmen Almazor (2018) showed that men have a greater tendency to use Islamic banks. Haider, Changchun, Akram, & Hussain (2018) stated that there are significant differences in intention to adopt Islamic mobile banking in Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Ayyub et al (2019), in their study on 264 users and non-users of Islamic banking in Pakistan, found that perceived behaviour control and usefulness are the most significant predictors of intention to use Islamic banking among users and non-users. Haider, Changchun & Akram (2018) found that perceived usefulness positively affects adopting Islamic mobile banking. Its influence on the male was stronger than females, while the perceived financial cost is negatively related to the adoption of Islamic m-banking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While the literature provides many models to study technology acceptance, TAM has been the most widely applied theoretical model (Suhartanto, 2019b). Simplicity and ease of implementation are some of the key reasons for the popularity of TAM over other frameworks (Haider, Changchun & Akram, 2018). However, TAM has many limitations: (i) many significant factors are not included in the model.…”
Section: Etam Modelmentioning
confidence: 99%
See 1 more Smart Citation